Cerebrospinal fluid neopterin in paediatric neurology: a marker of active central nervous system inflammation - Russell C. Dale; Fabienne Brilot; Elizabeth Fagan; John Earl (2009)
Cerebrospinal fluid (CSF) neopterin production is increased by interferon-gamma stimulation and appears to act as a marker of intrathecal immune activation. We aimed to test the usefulness of elevated CSF neopterin as a biological marker of central nervous system (CNS) inflammation.We retrospectively reviewed CSF neopterin in 158 children (89 males, 69 females, mean age 4y 1mo, SD 3y 11mo, range 1mo-15y).CSF neopterin levels in children with chronic static CNS disorders (n=105) were predominantly low, suggesting that inflammation is rare in these patients. We created an upper value of normal (chronic static group 95th centile 27.4 nmol/l). CSF neopterin was elevated in all 10 patients with acute encephalitis and in 10 of 12 patients with other acute inflammatory CNS disorders (demyelination, post-infectious ataxia, myelitis). CSF neopterin was also significantly elevated in patients with chronic progressive disorders of inflammatory origin. Interestingly, CSF neopterin was elevated in four of six patients with chronic static disorders who were tested during a febrile exacerbation of seizures or dystonia, suggesting that intrathecal immune activation may be important in this setting.Neopterin has a short half-life and was useful for monitoring inflammation activity in a patient with relapsing-remitting encephalitis. CSF neopterin is a useful marker of inflammation in a broad range of acute and chronic CNS disorders, and is a significantly more sensitive marker of inflammation than CSF pleocytosis.